Mechanisms of Action And Clinical Implications of MicroRNAs in the Drug Resistance of Gastric Cancer - Liu, Ying; Ao, Xiang; Ji, Guoqiang; Zhang, Yuan; Yu, Wanpeng; Wang, Jianxun (Frontiers in Oncology, 2021)
Gastric cancer (GC) is one of the most common malignant tumors of digestive systems worldwide, with high recurrence and mortality. Chemotherapy is still the standard treatment option for GC and can effectively improve the survival and life quality of GC patients. However, with the emergence of drug resistance, the clinical application of chemotherapeutic agents has been seriously restricted in GC patients. Although the mechanisms of drug resistance have been broadly investigated, they are still largely unknown. MicroRNAs (miRNAs) are a large group of small non-coding RNAs (ncRNAs) widely involved in the occurrence and progression of many cancer types, including GC. An increasing amount of evidence suggests that miRNAs may play crucial roles in the development of drug resistance by regulating some drug resistance-related proteins as well as gene expression. Some also exhibit great potential as novel biomarkers for predicting drug response to chemotherapy and therapeutic targets for GC patients. In this review, we systematically summarize recent advances in miRNAs and focus on their molecular mechanisms in the development of drug resistance in GC progression. We also highlight the potential of drug resistance-related miRNAs as biomarkers and therapeutic targets for GC patients.